B cell receptor repertoire analysis from autopsy samples of COVID-19 patients - Iwabuchi, Sadahiro; Tsukahara, Tomohide; Okayama, Toshitugu; Kitabatake, Masahiro; Motobayashi, Hideki; Shichino, Shigeyuki; Imafuku, Tadashi; Yamaji, Kenzaburo; Miyamoto, Kyohei; Tamura, Shinobu; Ueha, Satoshi; Ito, Toshihiro; et al. (Frontiers in Immunology, 2023)
Neutralizing antibodies against the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are being developed world over. We investigated the possibility of producing artificial antibodies from the formalin fixation and paraffin-embedding (FFPE) lung lobes of a patient who died by coronavirus disease 2019 (COVID-19). The B-cell receptors repertoire in the lung tissue where SARS-CoV-2 was detected were considered to have highly sensitive virus-neutralizing activity, and artificial antibodies were produced by combining the most frequently detected heavy and light chains. Some neutralizing effects against the SARS-CoV-2 were observed, and mixing two different artificial antibodies had a higher tendency to suppress the virus. The neutralizing effects were similar to the immunoglobulin G obtained from healthy donors who had received a COVID-19 mRNA vaccine. Therefore, the use of FFPE lung tissue, which preserves the condition of direct virus sensitization, to generate artificial antibodies may be useful against future unknown infectious diseases.